Efektifitas Perawatan Luka Modern Kombinasi Mendengarkan Musik Klasik Terhadap Penyembuhan Ulkus Diabetik Di Rumah Luka Surabaya - Imroatul Farida; Diyah Arini; Risca Putri Mardayati (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2018)
Diabetic ulcer need a long time for its healing process, failure during healing process of chronic wounds caused by necrotic tissue which becomes something foreign object for body and infected wounds. Proper wound care is needed to prevent wound complications. In this modern day, dressings combination of classical music becomes one of the diabetic ulcer therapy, this study aims to analyze the affectivity dressing combination of classical music to the acceleration of healing of diabetic ulcers at Rumah Luka Surabaya. Design of this study uses Quasi Experimental that is done by pre-test post-test in  treatment group and control group. Total population in this study is 35 patients with diabetic ulcers in the Rumah Luka Surabaya, using random sampling from Probability sampling technique and obtained 32 people as sample which divided into 2 groups: 16 people in control group and 16 groups in treatment group. Furthermore tested by using Two sample T test that results are modern influences dressing combination of classical music to healing diabetic ulcers are indicated by p 0.001 <α 0:05 means there is an influence of classical music therapy in the treatment group. The implications of this study can serve as a reference for future studies related to wound healing. In addition, further studies should be done to reinforce the concept centers on a diabetic ulcer care in managing diabetic ulcers in patients with diabetes mellitus.Keywords: Classic Music, Diabetic Ulcer, Modern Dressing